Financial education: Impact on the finances of mexican society (Revista de Investigaciones Universidad del Quindío, 2022)
Education represents the obtaining of knowledge for the development and learning of each person, through various methods and tools for its correct application. In the financial field, education represents the teaching of how to manage one's own resources avoiding unnecessary expenses and using financial products for better economic performance. The research carried out will describe how having a financial education can cause a great impact within the finances of each person, family, student, since having sufficient knowledge about finance can have better financial control, gradually generating their own wealth.
Keywords: economic growth; education; financial education; finance